Analysis Student Motivation and Learning Satisfaction in the Implementation of Statistics Application in Maritime Sector - Jabnabillah, Faradiba (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
The purpose of this study was to describe the differences in the average value of learning motivation and student satisfaction in Mathematics lessons by applying statistical applications. This study used an experimental method with a One Group Pretest Posttest design. The subjects in this study were grade XII IPA students at SMA N 21 Batam. The average pretest score from the student motivation questionnaire was recorded at 80.5. After applying statistical applications in mathematics learning, the average posttest score increased to 96.4. Furthermore, the average pretest score from the student satisfaction questionnaire was 83.2. Moreover the average posttest score of students after applying statistical applications in mathematics learning increased to 99.2. The results of statistical analysis using Paired Sample t-Test, found a significance value (Sig. 2-tailed) of learning motivation and student satisfaction of 0.000 < 0.05. Thus, the null hypothesis (H0) is rejected, which indicates a significant difference between the pretest and posttest scores for both motivational material and student satisfaction after the statistical application was applied.